A Time to Act : Address to the Board of Governors, Washington, DC, September 29, 2002 - Wolfensohn, James D. (Washington, DC: World Bank, 2013)
This is the address to the Board of Governors, delivered by Mr. James D. Wolfensohn, President of the World Bank. It was indicated that the development community has confirmed the Millennium Development Goals as our framework for action. Our thinking and action must be local, regional, and global, and we must work and act together. First and foremost, developing country leaders have asserted that the responsibility for the future of their countries is in their hands. They know that they must drive their development and create a constructive environment to encourage growth that is equitable and just for poor people, indeed for all people. This growth must be based on sound social and economic policies. To create the conditions for entrepreneurship, productivity, and jobs, the developing countries must invest in health and education, including early childhood education. These countries must also invest in effective legal and judicial systems; clear tax and regulatory frameworks implemented in approaches that fight corruption at all levels; and strong and well-regulated financial systems. It was also indicated that the Bank must focus on implementation of our promises to work toward the Millennium Development Goals. Our operations must become more transparent. We must support developing countries to better build their capacity. We must act now on our promises. We must deliver on them with a sense of urgency. This is our responsibility and our destiny.